A case study of science teachers' goal conflicts arising when integrating engineering into science classes. Issue 1 (25th October 2021) - Hutner, Todd L.; Sampson, Victor; Chu, Lawrence; Baze, Christina L.; Crawford, Richard H.
Abstract: The Framework for K‐12 Science Education details new goals to guide improvement of US science education. Among the new goals, the inclusion of engineering core ideas and practices stand out. We report a case study of four 8th‐grade science teachers who chose to integrate engineering core ideas and practices into their science classes by teaching four STEM design challenges (SDC). This study focuses on understanding the goal conflicts arising from these teachers' choice and how they resolve their goal conflicts. Primary data come from semistructured interviews conducted with each teacher. The goal conflicts expressed by our teachers fell into one of two broad categories: pacing conflicts and mandated testing conflicts. Pacing conflicts exist between the goals of teaching the SDCs in full and the goals of following the district‐wide pacing guide and covering all state mandated standards. Mandated testing conflicts were those goal conflicts arising between teaching the SDCs and ensuring that students were successful on officially mandated tests from the state and the district. The science teachers resolved their conflicts through goal balancing, where actions taken to satisfy one goal (teaching the SDCs) allow a person to subsequently pursue actions toward satisfying a conflicting goal. In this study, goal balancing is exhibited by teachers partially completing each SDC before moving on to the next topic. Finally, we discuss these findings in relationship to the existing literature on science teachers' goals and provide implications for science teachers' professional development and for research.